The country is different ministry and hope for rural Australia - Hawkes, Nicholas, 1953-; Joint Board of Christian Education (Melbourne, VIC The Joint Board of Christian Education, 1995)
Includes bibliographical references.
Keywords: Rural churches -- Australia; Rural ministry -- Australia